Implementation of Skills for Life for an Appropriate Approach to Men’s Conflicts: A View from the New Masculinities - Porras Quirós, Wilbert (2013)
This paper refers to the implementation of skills for life for an appropriate approach to men’s conflicts: a view from the new masculinities. The objective is to understand how the implementation of the skills for life approach can contribute to find alternatives that would promote prevention, as well as an appropriate approach to conflicts and conflict resolution by male population. It studies the main canons of masculinity, conflict resolution, and skills for life. It concludes calling attention to the implementation of skills for life in the strengthening of masculinities raising awareness of the importance of gender equality and equity as part of self-fulfillment.